Multidisciplinary approach to treatment with immune checkpoint inhibitors in patients with HIV, tuberculosis, or underlying autoimmune diseases - Aguilar-Company, Juan; Lopez-Olivo, Maria A.; Ruiz-Camps, Isabel (Frontiers in Medicine, 2022)
We reviewed available information on the use of immune checkpoint inhibitors (ICIs) in populations with special conditions, namely, patients with HIV, tuberculosis, or underlying autoimmune disease. Available data show treatment with ICIs is safe in patients with HIV; it is advisable, however, that these patients receive adequate antiretroviral therapy and have an undetectable viral load before ICIs are initiated. Tuberculosis reactivation has been reported with the use of ICIs, possibly due to immune dysregulation. Tuberculosis has also been associated with the use of immunosuppressors to treat immune-related adverse events (irAEs). Active tuberculosis must be ruled out in patients with symptoms or signs, and selected patients may benefit from screening for latent tuberculosis infection, although more data are required. Limited data exist regarding the safety of ICIs in patients with cancer and autoimmune disease. Data from observational studies suggest that up to 29% of patients with a preexisting autoimmune disease treated with an ICI present with an autoimmune disease flare, and 30% present with a de novo irAE of any type. Frequency of flares appears to differ according to the type of ICI, with higher rates associated with PD-1/PD-L1 inhibitors. Most common autoimmune diseases for which patients reported flares with ICI therapy are rheumatoid arthritis, other inflammatory arthritis, and psoriasis. Most studies have reported flares or de novo irAEs associated with ICIs that were mild to moderate, with low rates of discontinuation and no related deaths. Therefore, the use of ICIs in these patients is possible, but careful monitoring is required.